Personal branding in the knowledge economy the inter-relationship between corporate and employee brands - Kucharska, Wioleta, 1977- (New York, NY : Routledge, 2022)
Personal Branding in the Knowledge Economy: The Interrelationship between Corporate and Employee Brands aims to contribute to the academic debate about the marketization of individuals' knowledge, creativity, and personal images, alongside a growing interest in the whole area of branding in the networked economy based on knowledge. Personal branding and personal knowledge are critical assets of knowledge workers and key drivers of their development and innovative performance. Both strongly influence the individual success of knowledge workers in the networked and knowledge-driven economy. Personal brands are dynamically shifting from the side-lines to the center of the modern economy and the authenticity of the brands of personal ingredients for their ability to create value. They are one of the three key pillars of value creation in the social media environment, therefore significantly contribute to digital business models. The book will be of interest to researchers, academics, professionals, and students in the fields of organizational branding, marketing, management, and communications.
Keywords: BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Organizational Behavior; BUSINESS & ECONOMICS / Public Relations; Branding (Marketing); Knowledge economy; Business networks